Competitiveness challenge : transnational corporations and industrial restructuring in developing countries (UN New YorkUS, 2000)
Focuses on the impact of foreign direct investment (FDI) on industrial restructuring in selected industries in some developing countries. Examines how FDI affects the ability of economic actors - directly, foreign affiliates, and indirectly, local firms or the economy at large - to compete better in a globalizing world, primarily by raising, upgrading and diversifying exports.
Keywords: FOREIGN INVESTMENT